Intergovernmental Fiscal Relations : The Chinese System in Perspective - Arora, Vivek (IMF Working Papers; Working Paper, 1997)
This paper provides an overview of recent Chinese reforms to introduce a modern system of fiscal federalism that balances the need for central macroeconomic control with the economic advantages of decentralized government. Following a discussion of the rationale for decentralization, the paper describes the main structural and economic developments in China in this area, including their impact on economic stabilization. The key measures in the 1994 fiscal reforms as well as reform initiatives needed in the future are also discussed.